2019
DOI: 10.1021/acs.joc.9b02026
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenative Deuteration of Unactivated Alkyl Halides Using D2O as the Deuterium Source

Abstract: The general dehalogenation of alkyl halides with zinc using D2O or H2O as a deuterium or hydrogen donor has been developed. The method provides an efficient and economic protocol for deuterium-labeled derivatives with a wide substrate scope under mild reaction conditions. Mechanistic studies indicated that a radical process is involved for the formation of organozinc intermediates. The facile hydrolysis of the organozinc intermediates provides the driving force for this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 89 publications
2
9
0
Order By: Relevance
“…The combined organic layers were washed with hydrochloric acid (1 mol/L, 90 mL), dried over MgSO 4 and evaporated to yield the title compound 9b (225 mg, 1.58 mmol, 86 %, based on 42 % purity established by 1 H NMR) as a colorless liquid. The spectroscopic data were in accordance with the literature and with those of the product of the catalytic hydrogenation [44] …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The combined organic layers were washed with hydrochloric acid (1 mol/L, 90 mL), dried over MgSO 4 and evaporated to yield the title compound 9b (225 mg, 1.58 mmol, 86 %, based on 42 % purity established by 1 H NMR) as a colorless liquid. The spectroscopic data were in accordance with the literature and with those of the product of the catalytic hydrogenation [44] …”
Section: Methodssupporting
confidence: 82%
“…13 C{ 1 H} NMR (75 MHz, CDCl 3 ): δ =14.29 (2×CH 3 ), 22.86 (2×CH 2 ), 29.53 (2×CH 2 ), 29.83 (2×CH 2 ), 32.09 (2×CH 2 ) ppm. All spectroscopic data were in accordance with the literature [44] . C 10 H 22 (142.29) (b) Through diimide reduction of 5‐decene (10b) .…”
Section: Methodssupporting
confidence: 71%
“…The Br/D exchange reactions of arenes could also occur in a palladium-catalyzed system with a deuterium-labeled formate salt as the deuterium source. [23] Xia et al [24] developed zinc catalysts for the dehalogenation of alkyl halides and obtained deuterium-labeled derivatives using D 2 O as the deuterium donor. They also found that the formation and hydrolysis of organozinc intermediates were beneficial for this reaction.…”
Section: Dehalogenative Deuterationmentioning
confidence: 99%
“…Various electron-poor and electron-rich para -substituted cinnamaldehydes underwent deuteration at the α-position in good yield ( 2a – 2g ). In the case of 2h , deuterium incorporation was observed at both the α position and the positions ortho to the aniline group, likely caused by acid-mediated S E Ar with D + …”
mentioning
confidence: 99%
“…In the case of 2h, deuterium incorporation was observed at both the α position and the positions ortho to the aniline group, likely caused by acid-mediated S E Ar with D + . 17 Notably, the reaction could tolerate a S VI -containing substrate and afforded the product 2i in good yield with nearly full H/D exchange. The reaction scope was further explored for other substituted and unsubstituted cinnamaldehydes, which were all tolerated (2j−2o).…”
mentioning
confidence: 99%